MicroRNA-10a/b inhibit TGF-β/Smad-induced renal fibrosis by targeting TGF-β receptor 1 in diabetic kidney disease - Jinxiang Li; Shuling Yue; Jingwen Fang; Junling Zeng; Siqi Chen; Jianwei Tian; Sheng Nie; Xiaoting Liu; Hanying Ding (Molecular Therapy: Nucleic Acids, 2022)
TGF-β/Smad signaling plays a vital role in the development of fibrosis in diabetic kidney disease (DKD). However, remedies targeting key elements in TGF-β/Smad signaling are lacking. Here, we found that TGF-β receptor 1 (TGFBR1), a key protein in TGF-β/Smad signaling, was upregulated in kidney from diabetic mice and patients with DKD. Induction of TGFBR1 was regulated by microRNA-10a and -10b (miR-10a/b) by a post-transcriptional mechanism. Furthermore, the decreased XRN2, an exoribonuclease, was identified to contribute to affecting miR-10a/b maturation in vitro. In streptozotocin (STZ)-induced DKD mice, preventing the reduction of miR-10a/b in the kidney by an in situ lentivirus-injection method attenuated collagen deposition and foot process effacement, whereas deprivation of miR-10a/b aggravated renal fibrosis. Mechanistically, manipulating miR-10a/b in the kidney influenced TGFBR1 protein expression, TGF-β/Smad signaling activation, and downstream pro-fibrotic genes expression including fibronectin (FN) and α-smooth muscle actin (α-SMA). In a cohort of patients diagnosed DKD, renal miR-10a/b expressions were downregulated, whereas both TGFBR1 and fibrosis were enhanced. Our finding suggests that overexpressing miR-10a/b in kidney may be a promising method for the treatment of fibrosis in DKD.